Maternal hemodynamics in normal pregnancy and in pregnancy affected by pre‐eclampsia. (4th September 2018) - Stott, D.; Nzelu, O.; Nicolaides, K. H.; Kametas, N. A.
ABSTRACT: Objectives: To determine if, in a high‐risk group of women in the first half of pregnancy, those who develop pre‐eclampsia (PE) with fetal growth restriction (FGR) demonstrate distinct hemodynamics compared with those with PE in the absence of FGR (PE only). Methods: Cardiac output (CO), peripheral vascular resistance (PVR) and mean arterial pressure (MAP) were measured at the first hospital visit at 9–24 weeks' gestation in 69 women who had chronic hypertension and 67 who had had a hypertensive disorder in a previous pregnancy. These women were divided into five groups according to pregnancy outcome. In total, 19 subsequently developed PE only, 22 developed PE with FGR, 17 developed pregnancy‐induced hypertension, 39 had chronic hypertension without PE or FGR and 39 had had a hypertensive disorder in a previous pregnancy without PE, pregnancy‐induced hypertension or FGR in the index pregnancy. The hemodynamic values in each of these groups were compared with those in a cohort of 300 low‐risk women with normal pregnancy. Results: In all the high‐risk groups, PVR and MAP were higher than in women with a normal pregnancy, but CO was lower in the group of women with PE and FGR, whereas in the other high‐risk groups, it was not significantly different from normal. Conclusions: In women who develop PE, there is evidence of high PVR and MAP from the first half of pregnancy, whilst PE and FGR are associated with failure in physiological expansion of CO. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd. Abstract : Linked Comment: Ultrasound Obstet Gynecol 2018; 52: 302–303